Systematic study on the choice of higher education institutions in the engineering field - Torres, Arturo González; Avendaño-López, Pavel David Ulises; Bojorges, Gerardo Quiroz (Edelweiss Applied Science and Technology, 2025)
This research systematically examines the factors that influence the choice of higher education institutions in the field of engineering. Through a comprehensive review of recent literature, using the PRISMA 2020 methodology, 98 academic articles were analysed, of which 13 met the established inclusion criteria. The study identifies ten main factors influencing students’ decision, the most significant being family, educational and economic aspects, mentioned by 11-12 authors. Individual factors were cited by seven authors, while social and academic environment and gender stereotypes were mentioned by five and four authors respectively. The findings reveal that institutional choice is more influenced by external factors than by personal preferences. The research highlights the persistence of socio-cultural barriers in the selection of engineering careers and emphasises the need for educational policies that address these challenges. The results provide valuable information for educational institutions and policy makers, suggesting the implementation of more robust financial support and career guidance programmes to optimize engineering education.